Manajemen Risiko Hukum sebagai Strategi Meningkatkan Kinerja Perusahaan pada Era Ekonomi Digital - Muhammad Husaini (Genius: Jurnal Ekonomi Dan Manajemen, 2026)
The transformation of the digital economy has increased innovation opportunities while increasing legal risks that can affect company performance. This research aims to analyze the role of legal risk management as a strategy in improving company performance in the digital economy era. This study uses a qualitative approach with a phenomenological research type to understand the experience of organizational actors in managing legal risks. The data source consists of primary and secondary data; Primary data was obtained through in-depth interviews with company leaders, risk managers, compliance managers, and heads of legal divisions, while secondary data came from company documents, laws and regulations, governance reports, and relevant scientific literature. The results of the study show that legal risk management plays an important role in improving company performance through strengthening compliance, preventing disputes, protecting reputation, and improving adaptability to digital regulatory changes. Companies that systematically manage legal risks tend to be more operationally stable, more efficient in decision-making, and more trusted by stakeholders. Thus, legal risk management is not only a preventive instrument, but also an important strategy to strengthen the competitiveness and sustainability of companies in the digital economy era.